Penggunaan permainan monopoli untuk meningkatkan pemahaman konsep persatuan dan kesatuan pada kelas V sekolah dasar - Hutoyo, M N; Mahfud, Hasan; Adi, Fadhil Purnama (Jurnal Pendidikan Dasar, 2020)
Abstract. The purpose of this study is the use of monopoly games to improve understanding of the concept of unity. This research is a Classroom Action Research by conducting two cycles. The subject of this research is the fifth grade students of SDN Genengsari 3 Sukoharjo in the academic year 2019/2020 which has 25 students. This study uses data collection techniques in the form of interviews, observations, tests, and documentation with data validity data analysis and triangulation. Analysis of the data in this study uses the Miles-Huberman interactive analysis model. The first cycle obtained a percentage of 69% classically, and the second cycle research with a percentage of 90% in classical terms. Based on the results of the study, it can be concluded that the understanding of the concept of unity in 5th grade students of SDN Genengsari 3 Sukoharjo in the academic year 2019/2020 can be improved by the use of monopoly games.                 Keywords: elementary school, unity, monopoly game, civic education